Student’s Engagement and Perception of Gamification in Mathematics - Heny Solekhah; Imam Darul Kutni; Ario Bagus Pamungkas (Research Synergy Foundation, 2023)
Many Indonesian students consider mathematics as an uninteresting learning subject that confuses them. An innovative approach to teach mathematics is needed to increase their engagement. In this case study, gamification which has been known as an activity to increase the student’s enthusiasm was introduced in learning algebra. An observation with 20 female eighth graders was done in the classroom with and without the gamification activity to see the students’ reactions and emotions in playing the game. Two focus group discussions with eight students were conducted by purposeful sampling based on their various levels of activeness, and, competence in mathematics, as well as their scores of the game to grasp their perceptions of gamification in mathematics, followed by an individual interview with the math teacher. The findings were analyzed through the lenses of symbolic interactionism in which the students’ acts and perceptions were constructively interpreted and confirmed with the teacher’s opinion. The literature was also included to strengthen the result. The research found that gamification in mathematics could highly engage the students, especially when the teacher offered a reward. However, the student’s perception was highly influenced by their performance in the game. Despite the lack of mechanical skill, the winners were satisfied; the unsuccessful players had different opinions: some of them wanted to play again to increase their scores whereas the rest of them did not suit the game. Thus, to motivate the students, designing gamified activities in mathematics needed to consider individual preferences.